2011
DOI: 10.1016/j.intimp.2011.04.014
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 and TLR4 expression after kidney ischemia and reperfusion injury in mice treated with FTY720

Abstract: Ischemia and reperfusion injury (IR) is an antigen independent inflammatory process that causes tissue damage. After IR, kidneys up-regulate leukocyte adhesion molecules and toll-like receptors (TLRs). Moreover, injured kidneys can also secrete factors (i.e. heat shock protein) which bind to TLRs and trigger intracellular events culminating with the increase in the gene expression of inflammatory cytokines. FTY720 is an immunomodulatory compound and protects at least in part kidneys submitted to IR. The mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…In the present study, the TLR4 mRNA expression levels in the kidneys were markedly increased in the HS5 and HS10 groups compared with the control group, demonstrating that the kidneys were seriously impacted by AHS. In addition, previous research has shown a marked increase in TLR2 and TLR4 expression in renal tubular cells and in renal infiltrating cells caused by ischemia and reperfusion injury compared with control group (Kim et al, 2005;Pedregosa et al, 2011). Cunningham et al (2004) reported that TLR4 expression in the kidneys was critical in mediating LPS-induced acute kidney failure via proinflammatory cytokine release and subsequent kidney damage.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, the TLR4 mRNA expression levels in the kidneys were markedly increased in the HS5 and HS10 groups compared with the control group, demonstrating that the kidneys were seriously impacted by AHS. In addition, previous research has shown a marked increase in TLR2 and TLR4 expression in renal tubular cells and in renal infiltrating cells caused by ischemia and reperfusion injury compared with control group (Kim et al, 2005;Pedregosa et al, 2011). Cunningham et al (2004) reported that TLR4 expression in the kidneys was critical in mediating LPS-induced acute kidney failure via proinflammatory cytokine release and subsequent kidney damage.…”
Section: Discussionmentioning
confidence: 96%
“…This means that down regulated TLR4 and TLR7 mRNA expression levels in the spleen are beneficial to its immune function. On the other hand, Pedregosa et al (2011) indicated that ischemia and reperfusion injury caused a significant increase of TLR2 and TLR4 expression levels in spleen cells. In the present study, the TLR4 mRNA expression levels in the spleen were consistent with those observed in the small intestine, which were significantly reduced in the HS2 group and markedly elevated in the HS10 group.…”
Section: Upregulation Of Tlr4 Mrna Expression Levels In Broiler Chickmentioning
confidence: 99%
“…The compound is a substrate for sphingosine kinases (SphK1 and SphK2); its phosphorylated form, FTY720-P, acts as an agonist of sphingosine 1-phosphate (S1P) receptors (S1P1, S1P3, S1P4, S1P5), binding to them with high affinity at sub-nano-molar concentrations (1). Several groups have shown that FTY720 increases allograft survival (2,3), promotes earlier recovery from ischemia and reperfusion injury (4), and attenuates autoimmune diseases (5,6). The mechanisms underlying the effects of FTY720 were first described as the sequestration of lymphocytes in the thymus and secondary lymphoid organs, thus preventing their migration to inflammatory sites.…”
Section: Introductionmentioning
confidence: 99%
“…In the early postoperative period, mRNA for TLR2 was dominant, then decreasing by the 30th day with simultaneous increase in expression for TLR4 and MyD88. Very quick activation of TLR2 and related intensified inflammatory reaction might be the result of significant extent of ischemia-reperfusion injury, which is confirmed by further observations [8]. Undoubtedly, TLR2 function blocking in the early reperfusion period inhibits production of inflammatory mediators and is beneficial for maintaining organ functioning [9].…”
Section: Discussionmentioning
confidence: 52%